Three‐dimensional solubility parameters of natural rubber and its predictive power in diffusion coefficients. Issue 2 (31st July 2021) - Jing, Yuanrong; Cui, Ziwen; Zou, Huimin; Tu, Jieyun; Jiang, Xingwang; Shi, Xinghui; Yong, Zhanfu; Liu, Susu; Liu, Guangyong
Abstract: Equilibrium swelling test is employed to study the swelling responses of natural rubber (NR) in various solvents, and to determine the total Hildebrand solubility parameter ( δ t ) of NR. The three‐dimensional solubility parameters (HSP) of NR is obtained by virtue of software package as the result of being δ d  = 17.50 MPa 1/2, δ p  = 3.20 MPa 1/2, δ h  = 1.40 MPa 1/2, and δ t  = 17.85 MPa 1/2, respectively. The swelling ratio (q) is correlated with the energy difference (Ra) in order to deeply understand the swelling principle of NR, and the results turn out that q decreased with the increase of the Ra and it can be used to explain the abnormal swelling phenomena of methyl acetate and ethyl acetate. One of the possible applications of Ra is the prediction or explanation of diffusion behaviors of small liquids in the rubber matrix. Therefore, the diffusion coefficient (D) is calculated in accordance with the Fick's law model and attempted to correlate with the Ra value. Two qualitative relationships between D and Ra and χ HSP can be preliminarily established now, which can provide an easy way to predict the diffusion behavior of fluids in rubber matrix. Abstract :